Risk factors of drug abuse among Malay males FELDA settlers in Jerantut, Pahang - Mohd Khairi, Amir Faisal (2017)
Background: Globally, it is estimated that 246 million people had ever used illicit drugs. In Malaysia, drug abuse cases were on the rise, causing significant health and social problems for the people who use them, their families and communities. National Anti-Drug Agency (NADA) reported that 96.2% of drug abuse cases in Malaysia were among males. Jerantut, Pahang has the highest prevalence of registered drug abuse cases compared to other areas in the country and 70.3% of them are from FELDA settlements. Drug abuse places a heavy burden on public health systems in terms of treatment, care, prevention and their health consequences.